Impacto de infraestructura recreativa y cultural en los niveles de crimen locales de Bogotá, 2004-2015 (2017)
This document evaluates the impact of the construction and implementation of recreational-cultural infrastructure on the levels of different crimes at the local level. I used information of complaints received by the National Police and information of construction and opening of recreational and cultural infrastructure such as museums, libraries and houses of culture. The paper explores the difference in dates of delivery of cultural venues to analyze, through the method of differences in differences, the effect of these constructions on the level of crime in the area adjacent to its location. The results show that the delivery of a cultural or recreational venue has positive impacts on the reduction of "rational" crimes, mainly premeditated homicides and theft of motorcycles. On the other hand, the construction of this type of structure has no impact on the reduction of irrational crimes such as quarrels and personal injuries. Finally, I have not concluding results for crimes such as personal theft and drug trafficking, due to the quality of existing information for these crimes.--Tomado del Formato de Documento de Grado.